(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2023)
This article discusses the amendment regarding the provisions of alimony matters with its enactment before independence, which is the Shariah Law Administration Enactment (Selangor) 1952 (Enactment No. 3). However, for residents of Kuala Lumpur, this enactment was discontinued when the Federal Territory of Kuala Lumpur was established in 1974 with the enactment of the Islamic Family Law (Federal Territories) Act 1984 (Act 303). From the said formulation, this article examines the changes that occurred in the amendment on alimony. Among the studies conducted is whether there is a change in terms of Shariah or only in administration. In addition, there is also a question of enforcement if the alimony is not implemented by the person ordered, and whether it is improved or maintained without any amendment. The purpose of this study is to see the compatibility of the changing times with the amendment of Enactment No. 3 to Act 303 as well as through changes in terms of Shariah. This study uses data collection method, namely library research. The discussion concerns legal statutes only. In addition, related documents such as journal papers, fiqh books and previous studies were also used. The results of the study found that there are only five amendments from Enactment No. 3 to Act 303 and one to Act 585. The amendment of the five provisions involves the period of iddah alimony, the period of child alimony, alimony bearer, illegitimate child alimony and changes and cancellation of alimony. Out of the five provisions, only one provision involves Shariah, while the other four involve administration only. The latter involves the enforcement of law, amended from Enactment No. 3 to Act 585, which is more detailed and systematic. Keywords: The Syarak Law Administration Enactment (Selangor) 1952, alimony, amendment, Islamic family law, law, Shariah Court Full Text: PDF